Epidemiological Differences Between Localized and Nonlocalized Low Back Pain. Issue 10 (15th May 2017) - Coggon, David; Ntani, Georgia; Walker-Bone, Karen; Palmer, Keith T.; Felli, Vanda E.; Harari, Raul; Barrero, Lope H.; Felknor, Sarah A.; Gimeno, David; Cattrell, Anna; Vargas-Prada, Sergio; Bonzini, Matteo; et al.
Abstract : Study Design: A cross-sectional survey with a longitudinal follow-up. Objectives: The aim of this study was to test the hypothesis that pain, which is localized to the low back, differs epidemiologically from that which occurs simultaneously or close in time to pain at other anatomical sites Summary of Background Data: Low back pain (LBP) often occurs in combination with other regional pain, with which it shares similar psychological and psychosocial risk factors. However, few previous epidemiological studies of LBP have distinguished pain that is confined to the low back from that which occurs as part of a wider distribution of pain. Methods: We analyzed data from CUPID, a cohort study that used baseline and follow-up questionnaires to collect information about musculoskeletal pain, associated disability, and potential risk factors, in 47 occupational groups (office workers, nurses, and others) from 18 countries. Results: Among 12, 197 subjects at baseline, 609 (4.9%) reported localized LBP in the past month, and 3820 (31.3%) nonlocalized LBP. Nonlocalized LBP was more frequently associated with sciatica in the past month (48.1% vs . 30.0% of cases), occurred on more days in the past month and past year, was more often disabling for everyday activities (64.1% vs . 47.3% of cases), and had more frequently led to medical consultation and sickness absence from work. It was also more often persistent when participants were followed up after a mean of 14 months (65.6% vs . 54.1% of cases). In adjusted Poisson regression analyses, nonlocalized LBP was differentially associated with risk factors, particularly female sex, older age, and somatizing tendency. There were also marked differences in the relative prevalence of localized and nonlocalized LBP by occupational group. Conclusion: Future epidemiological studies should distinguish where possible between pain that is limited to the low back and LBP that occurs in association with pain at other anatomical locations. Level of Evidence: 2